Integrative metabolomics and microbiomics analysis reveals distinctive microbiota‐metabolites interactions in gastric carcinogenesis - Jiang, Xiao‐Wen; Zhang, Li; Liu, Zong‐Chao; Zhou, Tong; Li, Wen‐Qing; Liu, Wei‐Dong; Zhang, Lan‐Fu; You, Wei‐Cheng; Zhang, Yang; Pan, Kai‐Feng (International journal of cancer, 2025)
Gastric microbiota and metabolites may interact and play collaborative roles in the carcinogenesis process. This study aims to investigate differential metabolites and microbes, as well as the possible roles of microbe‐metabolite interactions in gastric cancer (GC) development. Targeted metabolomics assays and 16S rRNA sequencing were performed to compare metabolic and microbial profiles in gastric tissues from subjects with superficial gastritis/chronic atrophic gastritis (SG/CAG), intestinal metaplasia/low‐grade intraepithelial neoplasia (IM/LGIN) and GC. Significant differences were found in metabolic and microbial profiles between the GC and SG/CAG or IM/LGIN groups, respectively (all p < .05). By comparing GC with the other lesions, 69 differential metabolites mainly comprised triglycerides and phosphatidylcholines, and 21 differential microbes included Peptostreptococcus, Lactobacillus, Dialister, Helicobacter pylori, and Streptococcus anginosus (all p < .05). The altered metabolites and microbes in GC were both significantly enriched in the glycerophospholipid metabolism pathway, in which the predicted down‐regulation of phospholipase C (plc) and up‐regulation of 1‐acyl‐sn‐glycerol‐3‐phosphate acyltransferase (plsC) by microbiota may affect phosphatidylcholine hydrolysis and triglyceride biosynthesis modules. More and stronger microbe‐metabolite correlations in GC compared to the other lesion group further supported the potential microbial regulations to the important metabolites in gastric carcinogenesis, such as Lactobacillus and phosphatidylcholines (.32 ≤ r ≤ .57, all p < .05), Peptostreptococcus (.36 ≤ r ≤ .60, all p < .05) or Dialister (.36 ≤ r ≤ .62, all p < .05) and triglycerides. We simultaneously identified differential metabolites and microbes and their altered correlations between GC and gastric lesions. The main GC‐associated phosphatidylcholines and triglycerides may be affected by gastric microbes, which provides new perspectives on the microbiota‐metabolite interactions during the development of GC. What's New? Interactions between metabolites, microorganisms, and host factors in the stomach potentially influence gastric carcinogenesis. Little is known, however, about the microbes and metabolic pathways that are relevant to gastric cancer (GC). In the present study, the authors elucidated gastric metabolomics and microbiomics profiles and, using targeted metabolomics profiles, explored microbe‐metabolite interactions in both GC and precancerous gastric lesions. GC and gastric lesions differed in metabolic and microbial profiles, particularly with regard to triglyceride and phosphatidylcholine metabolites and microbes such as Peptostreptococcus, Dialister, and Lactobacillus. These microbes appear to influence GC through the regulation of functional orthologs involved in glycerophospholipid metabolism.